: Función de producción de la mora de castilla en la parroquia San Luis, cantón Riobamba, provincia de Chimborazo. - Allauca Amaguaya, Marcia Jhoana (2024)
ABSTRACT: The objective of this research is to estimate the production function of blackberry from Castilla in the San Luis parish, in the Riobamba canton, province of Chimborazo, in order to find the participation of the production factors and the type of scale performance that it presents, for the year 2023. 75 surveys were applied to blackberry producers from Castilla, with the information obtained the Cobb Douglas production function was estimated, through which the elasticities were obtained to evaluate the type of scale performance and the participation that each of the productive factors capital and labor has with respect to the quantity of blackberries harvested. The results achieved explain that the factors of labor and capital have a participation of 0.15 and 0.71 respectively, therefore, for every 1% that labor and capital vary, the amount harvested will vary in the same direction by 0.15%. and 0.71%. According to the applied model, it was obtained that the cost of labor and the cost of capital show significant coefficients. Likewise, the production of blackberry from Castilla presents decreasing returns to scale, since the sum of the elasticities was 0.87 less than 1. Finally, blackberry producers invest more in the capital factor while labor has a significant contribution to the production process, returns are decreasing because there is not enough participation of labor, so when the factors increase simultaneously, the production obtained will grow, but in a limited or smaller proportion than the amount invested.